Antigen presentation by supported planar membranes containing affinity-purified I-Ad. - Watts, T H (1984)
I-Ad, purified from A20-1.11 cells by affinity chromatography, was incorporated into supported planar membranes by incubation of I-Ad-containing phospholipid vesicles with clean glass coverslips. Such planar membranes present a peptide digest of ovalbumin to the ovalbumin-specific, I-Ad-restricted T-cell hybridoma 3DO-54.8, resulting in the antigen-specific release of interleukin 2. However, when the same material was provided in the form of small unilamellar vesicles, no response was obtained. Antigen presentation by the I-Ad-containing planar membranes was inhibited by the monoclonal antibody MKD6 (anti-I-Ad) but not by the antibody 10-2.16 (anti-I-Ak). The antibody GK1.5, which recognizes the T-cell surface antigen L3T4, was also inhibitory. In contrast to the results with purified I-Ad, crude membrane preparations from A20-1.11 cells were effective in antigen presentation in both planar and vesicular forms.